Moderate-to-vigorous intensity physical activity levels of children with intellectual disability during physical education classes - Hao, Yaru; Razman, Rizal (Frontiers in Public Health, 2023)
Background Physical education (PE) class is an excellent way to improve moderate-to-vigorous intensity physical activity (MVPA). Increasing number of research has explored the children’s PA based on movement during PE classes, but data for children with intellectual disability (ID) is still lacking. Purpose The purpose of this study was to investigate the current status of MVPA levels of children with ID during PE classes in China, as well as differences of MVPA levels according to gender and grade. Methods Accelerometers were used to record MVPA levels of fifty-three children with severe ID from 9 to 16 years of age (mean age: 12.60 ± 1.66 years) during standard PE classes. Results The mean time spent in MVPA during PE classes was 8.00 ± 2.10 min, meaning only 22.88% of PE class time was spent in MVPA. As grade levels progresses, time spent in MVPA during PE classes tended to decrease; the fourth-grade children tended to spend more time in MVPA during PE classes compared with the fifth-grade and the sixth-grade (9.15 vs. 7.61 vs. 7.25 min, all p < 0.05). Boys spend significantly more time in MVPA during PE classes than girls; both in the entire sample (9.20 vs. 5.70 min) as well as in each grade (9.76 vs. 6.09 min, 9.35 vs. 5.68 min, 8.31 vs. 5.59 min, all p < 0.05). Conclusion Findings from this study indicate that the proportion of PE class spent in the MVPA of children with ID was lower than the 50% recommended by the U.S. Department of Health and Human Services (DHHS) and U.K. Association for Physical Education (AfPE). And the amount of MVPA participation varied by the grade and gender as well as by the activity performed. Therefore, in order to help children with ID achieve MVPA goals, educators need to reevaluate the PE curriculum as well as take due consideration of grade and gender when devising new content.